PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PENDEKATAN SCIENTIFIC PADA SUBTEMA GAYA DAN GERAK - IIR, Iryanti (2014)
Berdasarkan studi pendahuluan peneliti menemukan guru jarang menggunakan media pembelajaran dengan baik serta learning obstacleterutama bersifat etimologis yang dialami siswa. Pendekatan yang peneliti gunakan adalah pendekatan kualitatifdengan metode Penelitian Desain Didaktis terdiri atas tiga tahap, yaitu Prospektif Analysis, Metapedadidaktik Analysis, dan Retrosfektif Analysis. Subjek dalam penelitian adalah siswa kelas IV Negeri 3 Benteng Kecamatan Ciamis dan SD Negeri 1 Cijeungjing Kecamatan Cijeungjing Kabupaten Ciamis. Teknik pengumpulan datadilakukan peneliti melalui proses triangulasi.Hasil penelitian diperoleh beberapa learning obstacle siswa yang disebabkan belum baiknya penggunaan media dan desain media pembelajaran untuk mengatasi learning obstacle siswa pada subtema Gaya dan Gerak pembelajaran kesatu. Desain media pembelajaran disusun berdasarkan learning obstacle siswa dan sesuai dengan komponen HLT. Desain awal media pembelajarandapat mengurangi learning obstacle siswa sebesar 12,103%, dan desain pengembangan media pembelajarandapat mengurangi learning obstacle siswa sebesar 16,18%. Kata Kunci: Learning obstacle, Desain didaktis, Subtema Gaya dan Gerak. The researchers founded incidence of teachers rarely use the well medias. And the researchers founded learning obstacles experienced by the students, especially about etymologically because not good use of instructional media. This study aimed to describe of learning obstacles experienced by the students, caused not good use of instructional media on learning the first Subtheme Forces and movement, developing a media construct the didactic design based learning scientific obstacle to overcome student learning, and implementation didactical design. The researchers used qualitative approach and design didactical research method consists of three stages, namely Prospective Analysis, Metapedadidaktik Analysis, and Retrosfektif Analysis. Subjects in the study were students of class IV School 3 Benteng Kecamatan Ciamis and SD Negeri 1 Cijeungjing Kecamatan Cijeungjing Kabupaten Ciamis. The researchers used triangulation process for code colected. The research showed some learning obstacles experienced by the students caused not well use of media and didactical design of instructional media development to overcome the obstacle of students learning the first Subtheme Forces and movement. Design didactical research obstacle compiled based on student learning and in accordance with the HLT components. The first design didactical can reduce students' learning of 12,103%, and the design second design didactical can reduce student learning obstacle by 16.18%. Keyword: Learning Obstacle, Didactical Design, Subtheme Forces and Movement